Fostering future entrepreneurs: The interplay of motivation and education in Malaysian universities - Ferdouse, Farzana; Sarwar, Abdullah; Khan, Nasreen; Siddika, Aysa (International Journal of Innovative Research and Scientific Studies, 2025)
Youth unemployment constitutes a substantial portion of the unemployed population, placing Malaysia’s economic landscape in a precarious position. Therefore, entrepreneurship education (EE) is important in developing young people’s entrepreneurial skills that can increase job creation and economic resilience by mitigating unemployment. However, a knowledge gap exists regarding how autonomous motivation (AM) and controlled motivation (CM) are integrated into students’ entrepreneurial aspirations. Therefore, this study aimed to bridge this gap by hypothesizing how motivation steers the intention to be an entrepreneur (EI) and the moderating role of entrepreneurship education (EE). The sample of this study consisted of 338 final-year students from private and public universities. PLS-SEM was utilized for data analysis. The study finds that AM and CM directly affect EI. However, the moderating effects of EE on AM, CM, and EI show mixed results. Although the effects of AM on EI remain consistent regardless of the level of EE granted, the level of EE does moderate the interaction between CM and EI, weakening CM's negative influence on EI. The findings provide valuable insights for policymakers in formulating entrepreneurship policies and suggest avenues for educational programs to foster entrepreneurial motivation among students.